Solubility of pyromorphite Pb5(PO4)3Cl at 5–65 °C and its experimentally determined thermodynamic parameters. (July 2016) - Topolska, Justyna; Manecki, Maciej; Bajda, Tomasz; Borkiewicz, Olaf; Budzewski, Przemysław
Highlights: Solubility of pyromorphite Pb5 (PO4 )3 Cl was determined in dissolution experiments. The new solubility constant for pyromorphite (PY) is Ksp, 298 = 10 −79.6 ± 0.15 . Thermodynamics of PY dissolution reaction were determined; it is endothermic. The Gibbs free energy of formation for PY is Δ G ° f = −3764.3 ± 3.5 kJ·mol −1 . The enthalpy of formation for PY is Δ H ° f = −4108.4 ± 7.9 kJ·mol −1 . Abstract: The solubility of synthetic pyromorphite Pb5 (PO4 )3 Cl was determined in a series of dissolution experiments conducted at 5–65 °C and at pH = 2.0. The equilibrium was established within 4 months. The dissolution of pyromorphite was congruent at all the temperatures, and the measured solubility product log Ksp, 298 for the dissolution reaction: Pb 5 ( PO 4 ) 3 Cl ⇔ 5 Pb 2 + + 3 PO 4 3 - + Cl - was determined to be −79.6 ± 0.15. The equilibrium ion activity product of pyromorphite increased with temperature, indicating a positive enthalpy of the dissolution reaction in the temperature range from 5 to 65 °C. The temperature dependence of the log Ksp was nonlinear: log Ksp = A − B / T + D log( T ), where A = 478.77 ± 136.62, B = 29, 378 ± 6215, and D = −185.81 ± 46.77. This allowed for calculation of Δ G ° r = 454.0 ± 1.7 kJ·mol −1, Δ H ° r = 101.8 ± 6.0 J·mol −1 ·K −1, Δ C ° p, r = −1545 ± 388.9 J·mol −1 ·K −1, and Δ S ° r = −1181 ± 382 J·mol −1 ·K −1 of the dissolution reaction. Using these values and the published standard state quantities for constituent ions, the values of Δ G ° f = −3764.3 ± 3.5 kJ·mol −1, Δ H ° f = − 4108.4 ± 7.9 J·mol −1 ·K −1, S ° f = 622 ± 382 J·mol −1 ·K −1, and C ° pf = 402 ± 398 J·mol −1 ·K −1 were calculated for synthetic pyromorphite Pb5 (PO4 )3 Cl.